Manajemen Kepemimpinan Pendidikan Islam pada Sekolah Internasional di Indonesia - Nailatsani, Fathinahaya; Akhmad, Fandi; Amalia, Ulfyana; Rosa, Dina (Lembaga Yasin AlSys, 2021)
Leadership is something that is felt to be quite important in the sustainability of an organization or group. A good leadership pattern will produce effective and efficient organizational or group dynamics. Likewise in the scope of education, good and structured leadership will make the achievement of the goals of education itself. Leadership management applied in education needs to be done as well as possible by looking at various considerations. In international school-based education, educational leadership needs to take diversity and culture into consideration. If focused on Islamic education, leadership management in international schools needs to be focused on achieving the vision and mission that has been prepared with various considerations. The visionary, innovative, and varied international school-based characteristics make the need for leadership management in Islamic education that is able to place Islamic education as a handle on the various dynamics that occur.